The Influence of Leadership on Employee Performance at the Office of the National Land Agency of Tangerang City - Sri Mulyani (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
This study aims to determine the influence of leadership on employee performance at the Office of the National Land Agency of Tangerang City. The method used is explanatory research with a sample of 85 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study of leadership variables obtained an average score of 3,391 with suitable criteria. Employee performance variable received an average score of 3.819 with applicable standards. Leadership has a positive and significant effect on employee performance with a regression equation value of Y = 12.861 + 0.747X. A correlation coefficient value of 0.712 or has a strong relationship with a determination value of 50.8%. Hypothesis testing obtained a significance of 0.000 <0.05.